Protein Kinase C-θ (PKC-θ) in Natural Killer Cell Function and Anti-Tumor Immunity - Anel, Alberto; Aguiló, Juan I.; Catalán, Elena; Garaude, Johan; Rathore, Moeez G.; Pardo, Julián; Villalba, Martín (Frontiers in Immunology, 2012)
The protein kinase C-θ (PKCθ), which is essential for T cell function and survival, is also required for efficient anti-tumor immune surveillance. Natural killer (NK) cells, which express PKCθ, play a prominent role in this process, mainly by elimination of tumor cells with reduced or absent major histocompatibility complex class-I (MHC-I) expression. This justifies the increased interest of the use of activated NK cells in anti-tumor immunotherapy in the clinic. The in vivo development of MHC-I-deficient tumors is much favored in PKCθ−/− mice compared with wild-type mice. Recent data offer some clues on the mechanism that could explain the important role of PKCθ in NK cell-mediated anti-tumor immune surveillance: some studies show that PKCθ is implicated in signal transduction and anti-tumoral activity of NK cells elicited by interleukin (IL)-12 or IL-15, while others show that it is implicated in NK cell functional activation mediated by certain killer-activating receptors. Alternatively, the possibility that PKCθ is involved in NK cell degranulation is discussed, since recent data indicate that it is implicated in microtubule-organizing center polarization to the immune synapse in CD4+ T cells. The implication of PKC isoforms in degranulation has been more extensively studied in cytotoxic T lymphocyte, and these studies will be also summarized.